Study of carbon dioxide absorption in fibrous mist collector - Waldberg, Arnold; Polienova, Evgenija (Journal of Environmental Engineering and Landscape Management, 2010)
Industrial tests of fibrous filters have shown that, above mist drop collecting, they are effective means for adsorption of gaseous impurities. Considering it, there were made tests that enabled reaching quantitative results on CO2 absorption by aqueous solution of sodium. Tests were made on experimental plant using apparatus with fibrous nozzle as its main element. Absorber studies were made in the laboratory of engineering ecology of municipal services at Moscow State University of Environmental Engineering (MSUEE). Experimental plant is automated: controlling and regulation of regime parameters of the absorber are made using the monitor of a personal computer.Article in Russian.Anglies dioksido absorbcijos pluoštinio rūko surinktuve tyrimaiSantrauka. Atlikus pluoštinių filtrų pramoninius tyrimus nustatyta, kad šie filtrai, laikomi virš rūko lašelių, efektyviai adsorbuoja dujose esancius nešvarumus. Atsižvelgiant į tai buvo atliekami tyrimai su natrio šarmo tirpalu ir gauti kiekybiniai CO2 absorbcijos rezultatai. Tirta eksperimentinimis salygomis naudojant prietaisus su pluoštiniu antgaliu. Absorberio tyrimai buvo atliekami Miestų inžinerinės ekologijos laboratorijoje Maskvos valstybiniame aplinkos inžinerijos universitete (AIMVU). Eksperimentinis tyrimas automatizuotas, absorberio režimo parametrai kontroliuojami ir reguliuojami asmeniniu kompiuteriu.Reikšminiai žodžiai: pluoštinis dangtelis, hidraulinis pasipriešinimas, absorbcija.Исследование абсорбции углекислого газа в волокнистом туманоуловителеРезюме. Промышленные испытания волокнистых фильтров показали, что помимо улавливания капель туманов, они достаточно эффективно поглощают и газообразные вредности. В связи с этим на экспериментальной установке, основным элементом которой являлся аппарат с волокнистой насадкой, были проведены исследования, позволившие получить количественные результаты по абсорбции СО2 водным раствором соды. Исследования абсорбера проводились в лаборатории кафедры «Инженерная экология городского хозяйства» Московского государственного университета инженерной экологии (МГУИЭ). Экспериментальная установка автоматизирована: контроль и регулировка режимных параметров абсорбера осуществляются с экрана персонального компьютера.Ключевые слова: волокнистая насадка, гидравлическое сопротивление, абсорбция.First Published Online: 14 Oct 2010